До характеристики концепції флексік’юріті при використанні нетипових форм зайнятості - Гусаров, О. С.; Husarov, O. S. (Науковий вісник публічного та приватного права. - 2023. - Вип. 4. - С. 53-58, 2023)
Розкрито сутність концепції флексік’юріті при використанні нетипових форм зайнятості. Доведено, що відповідна концепція закладає основи збалансованого поєднання гнучкості регулювання трудових відносин із забезпеченням належного рівня соціального захисту трудового населення, що є одним із ключових пунктів ефективного використання нетипових форм зайнятості. Наголошено, що в Україні доцільні поєднати переваги обох зазначених систем. Адже в нашій державі ідеї про посилення гнучкості в регламентуванні трудових відносин, передусім спричинили виникнення нових нетипових правовідносин, нетипових форм зайнятості, нетипових трудових договорів, однак ця нетиповість (або нестандартність) не повинна бути підставою для обмеження прав найманих працівників, які працюють за такими формами зайнятості, порівняно із працівниками, які залучені до праці у стандартних формах зайнятості. Окрім того, необхідно використати досвід реалізації датського підходу до здійснення державної політики у сфері праці, а саме забезпечити гідний рівень соціального захисту найманих працівників та безробітних, а також створити усі необхідні умови для професійного навчання людини протягом її трудового життя.

The relevance of the article lies in the fact that in recent years atypical forms of employment in Europe and the world are gaining more and more popularity, and Ukraine in this context is no exception. To date, in our country, the system of normative and legal regulation of this institute is still imperfect and needs comprehensive improvement. Reflecting on ways to improve labor legislation that regulates atypical forms of employment, it is worth emphasizing the need to develop and officially consolidate conceptual foundations for the use and development of such forms of employment, and also noted the importance of implementing relevant international norms and standards in this area. The purpose of the article is to provide a description of the concept of flexicurity when using atypical forms of employment. The article, based on the analysis of scientific views of scientists, reveals the essence of the concept of flexicurity when using atypical forms of employment. It has been proven that the relevant concept lays the foundations for a balanced combination of flexibility in the regulation of labor relations with the provision of an appropriate level of social protection of the working population, which is one of the key points of the effective use of atypical forms of employment. It was emphasized that in Ukraine it is expedient to combine the advantages of both mentioned systems. After all, in our country, ideas about increasing flexibility in the regulation of labor relations, first of all, caused the emergence of new atypical legal relationships, atypical forms of employment, atypical labor contracts, but this atypicality (or nonstandardity) should not be the basis for limiting the rights of employees who work under such forms employment, compared to employees who are engaged in work in standard forms of employment. In addition, it is necessary to use the experience of implementing the Danish approach to the implementation of state policy in the field of labor, namely to ensure a decent level of social protection for employees and the unemployed, as well as to create all the necessary conditions for professional training of a person during his working life. It was concluded that the introduction and implementation of the ideas and principles of the concept of flexicurity is an important and necessary step on the way to the development of atypical forms of employment in Ukraine. This concept lays the foundations for a balanced combination of flexibility in the regulation of labor relations with the provision of an adequate level of social protection of the working population, which is one of the key points of the effective use of atypical forms of employment.

Раскрыта сущность концепции флексикюрити при использовании нетипичных форм занятости. Доказано, что соответствующая концепция закладывает основы сбалансированного сочетание гибкости регулирования трудовых отношений с обеспечением должного уровня социальной защиты трудового населения, являющегося одним из ключевых пунктов эффективного использования нетипичных форм занятости.
To characterize the concept of flexicurity when using atypical forms of employment
Keywords: трудові відносини; labor relations; трудовые отношения; концепція; concept; концепция; flexicurity; флексикюрити; нетипова зайнятість; atypical employment; нетипичная занятость; правове регулювання; legal regulation; правовое регулирование; працівники; employees; работники